Activated carbon‐based composites for capturing CO2: a review. Issue 2 (2nd February 2021) - Wang, Junya; Pu, Qiuyun; Ning, Ping; Lu, Shijian
Abstract: Activated carbon is widely regarded as a potential CO2 adsorbent because of its special texture. Activated carbon captures CO2 mainly through physical adsorption due to the characteristics of surface structure and pore structure, which makes the adsorbent sensitive to temperature and relatively low in selectivity. In order to solve these problems, much effort has been made in new developments, including synthesis activated carbon‐based composites, which can not only improve its CO2 capture capacity and stability, but also improve its selectivity. This paper reviews the recent research focused on the activated carbon‐based composites using in postcombustion CO2 capture. The status and development of activated carbon‐based composites are presented in four parts as activated carbon/metal composite, activated carbon/zeolite composite, activated carbon/metal organic framework composite, and activated carbon/carbon material composite. The details of synthesis method, synthesis condition, modification method, and CO2 adsorption performance are introduced. Simultaneously, the characteristics, advantages, and potential challenges of the composites are also summarized. This work will provide important parameters in the applications of activated carbon‐based adsorbents for postcombustion CO2 capture and give suggestions on future research efforts. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd.